Study of the HARPS Line Profile Using a Laser Frequency Comb. Issue Volume 8:Issue S293(2012) (29th April 2014) - Zhao, F.; Curto, G. Lo; Pasquini, L.; Zhao, G.
Abstract: High precision spectroscopy is one of the most successful methods to detect extra-solar planets. To enable the detection of Earth-like planets in the habitable zone, extremely precise instruments are required. Our lack of knowledge of the instrument line profile, non-linearity and charge transfer efficiency effects in the detector limits the achievable precision of an instrument. We report our studies on the HARPS (High Accuracy Radial- velocity Planet Searcher) line profiles, measured using the unresolved lines of a Laser Frequency Comb (LFC). We show how the line profile changes as a function of position and signal, and estimate the errors made in the line centroid measurement due to the variation of the line profile.